English skills of young learners in Iceland : “I started talking English when I was 4 years old. It just bang… just fall into me.” - Samuel C. Lefever 1954- (2010)
Ráðstefnurit Netlu This article presents findings from a recent study of reading, listening and communication skills in English of Icelandic children. The study was carried out in five urban schools with children (age 8) who had not received formal English instruction. In addition, parents of the most competent children were asked to describe their children’s English learning and use in the home. The results of the study show that children begin to learn English outside of school at an early age in Iceland. Most children can understand basic spoken English and many can participate in simple conversations in English. Parents primarily attribute their children’s language learning to their exposure to English through media and computer games and their interest in learning English. Í greininni eru kynntar niðurstöður úr rannsókn sem hafði það að markmiði að kanna enskukunnáttu átta ára barna áður en formlegt enskunám þeirra hefst. Gögnum var safnað í fimm skólum á suðvesturhorninu. Kannaður var les- og hlustunarskilningur barnanna ásamt samtalsfærni þeirra á ensku. Foreldrar þeirra barna sem sýndu mestu samtalsfærnina voru beðnir að lýsa með hvaða hætti þau hefðu lært ensku. Niðurstöðurnar sýna að mörg börn eru byrjuð að skilja einfalt enskt talmál mjög snemma og nokkur fjöldi þeirra getur tekið þátt í einföldum samtölum á ensku. Áhugi barnanna á að læra ensku er mikill og aðgengi að ensku í daglegu umhverfi þeirra er töluvert. Þetta tvennt nefna foreldrar oftast sem skýringu á því hvernig börn þeirra hafa lært ensku.